Methods of test for petroleum and its products. Determination of polycyclic aromatics in unused lubricating base oils and asphaltene free petroleum fractions. Dimethyl sulphoxide extraction refractive index method Part 346, (15th July 1996) - British Standards Institution,
No abstract available